Sarcoidosis of the ear, nose and throat: A review of the literature. (8th June 2021) - Cereceda‐Monteoliva, Nicholas; Rouhani, Maral J.; Maughan, Elizabeth F; Rotman, Anthony; Orban, Nara; Al Yaghchi, Chadwan; Sandhu, Guri
Abstract : Objectives: Sarcoidosis is a multisystemic inflammatory disease with extrathoracic manifestations, most commonly affecting the young and middle‐aged, female and Black populations. Diagnosis usually requires evidence of non‐caseating granulomata and, when treated, prognosis is usually favourable. We aim to establish the incidence, clinical features and optimal treatment of ENT manifestations of this disease. Design: We performed a PubMed literature review to determine the evidence base supporting this. Results: ENT manifestations are present in 5%‐15% of patients with sarcoidosis, often as a presenting feature, and require vigilance for swift recognition and coordinated additional treatment specific to the organ. Laryngeal sarcoidosis presents with difficulty in breathing, dysphonia and cough, and may be treated by speech and language therapy (SLT) or intralesional injection, dilatation or tissue reduction. Nasal disease presents with crusting, rhinitis, nasal obstruction and anosmia, usually without sinus involvement. It is treated by topical nasal or intralesional treatments but may also require endoscopic sinus surgery, laser treatment or even nasal reconstruction. Otological disease is uncommon but includes audiovestibular symptoms, both sensorineural and conductive hearing loss, and skin lesions. Conclusions: The consequences of ENT manifestations of sarcoidosis can be uncomfortable, disabling and even life‐threatening. Effective management strategies require good diagnostic skills and use of specific therapies combined with established treatments such as corticosteroids. Comparisons of treatment outcomes are needed to establish best practice in this area.